A recyclable, recoverable, and reformable hydrogel-based smart photocatalyst. Issue 4 (14th March 2017) - Mai, Ngoc Xuan Dat; Bae, Joonwon; Kim, Il Tae; Park, Sung Hoon; Lee, Go-Woon; Kim, Ji Hyeon; Lee, Daeho; Son, Hyung Bin; Lee, Young-Chul; Hur, Jaehyun
Abstract : A TiO2 /agarose hybrid gel photocatalyst that is recyclable, recoverable, and reformable was fabricated and the optimal photocatalytic conditions were experimentally determined. Abstract : We present a novel hydrogel-based photocatalyst that contains TiO2 nanoparticles (NPs) uniformly dispersed in an agarose hydrogel matrix. The preparation of the TiO2 /agarose hybrid gel photocatalyst was based on the gelation of agarose in the presence of well-dispersed TiO2 NPs in hot water. TiO2 NPs were homogeneously distributed in the agarose gel as characterized by Fourier transform infrared spectroscopy (FT-IR) analysis. It was found that the size, uniformity, and concentration of the hybrid gel as well as the contents of constituent ingredients have significant effects on the photocatalytic activity. The smaller and uniform size of the hybrid gel at an appropriate concentration exhibited superior photocatalytic performance in both photodegradation of methylene blue (MB) under UV light and TiO2 leakage. In the moderate concentration range of TiO2 and agarose, the degradation rate of MB increased upon increasing the TiO2 content or decreasing the agarose concentration. Under the optimized conditions, our hybrid gel showed excellent recycling performance over repeated use. Furthermore, we demonstrate the additional excellent features of our hybrid gel, which are: i) regeneration of pure TiO2 NPs and ii) thermal reconstruction of the hybrid gel. During the recycling, the TiO2 NPs initially immobilized in the hydrogel could be recovered through the programmed heating and separation techniques. Also, our hybrid gel could be easily reshaped into a new hydrogel with a desired architecture in terms of its size and shape. These unprecedented properties make our hybrid gel a smart and cost-effective new promising material for use in practical waste/water treatment.